BIOM-25. ADULT GANGLIOGLIOMA: A 4-PATIENT CASE SERIES WITH MOLECULAR PROFILING. (12th November 2021) - Shen, Erica; Shams, Alireza; Song, Xianyuan; Daher, Ahmad
Abstract: Accounting for only 2% of all primary brain tumors, ganglioglioma is a rare neoplasm that most frequently arises in the temporal lobe in children or young adults. Ganglioglioma is the most common epilepsy-associated neoplasm and is typically composed of dysplastic ganglion cells and neoplastic glial cells. Recent publications have revealed that the activating p.V600E mutation in the BRAF oncogene is seen in 20-60% of gangliogliomas. However, the genetic landscape of ganglioglioma requires further elucidation, especially in gangliogliomas that arise from outside of the temporal lobe in adults. In this case series, we describe the genetic mutations of adult gangliogliomas originating outside of the temporal lobe in four patients aged 21 to 56 years. Targeted next generation sequencing via the MSK-IMPACT panel covering 500 actionable mutations was used in all cases. None of the cases had the BRAF p.V600E mutation. Case 1 describes a left cerebellar cystic ganglioglioma with NTRK2 fusion mutation ( NTRK2-DST ) and a tumor mutation burden (TMB) = 0 mutation/megabase (mut/Mb). Case 2 describes a right parietal lobe cystic ganglioglioma with a BRAF-CLEC2L inversion mutation and TMB = 0 mut/Mb. Case 3 describes a cerebellar vermis ganglioglioma with a BRAF fusion mutation ( BRAF-KIAA1549 ) and TMB = 0 mut/Mb. The last case describes a right cerebellopontine angle ganglioglioma with a MAP2K1 splicing mutation and TMB = 0.9 mut/Mb. To the best of our knowledge, the mutations identified in this case series have not been previously described in adult brain gangliogliomas. The BRAF-KIAA1549 fusion mutation has been found in spinal cord gangliogliomas, but not in brain gangliogliomas. MAP2K1 splicing mutations, unlike MAP2K1 in-frame deletions, have not been found in gangliogliomas. Finally, a different NTRK2 mutation ( NTRK2-TLE4 ) has been described in a pediatric ganglioglioma, but NTRK2-DST has not been found in any adult gangliogliomas.